Uncovering the link between the SpnIII restriction modification system and LuxS in Streptococcus pneumoniae meningitis isolates - Agnew, Hannah N.; Atack, John M.; Fernando, Ann R.D.; Waters, Sophie N.; van der Linden, Mark; Smith, Erin; Abell, Andrew D.; Brazel, Erin B.; Paton, James C.; Trappetti, Claudia (Frontiers in Cellular and Infection Microbiology, 2023)
Streptococcus pneumoniae is capable of randomly switching their genomic DNA methylation pattern between six distinct bacterial subpopulations (A-F) via recombination of a type 1 restriction-modification locus, spnIII. These pneumococcal subpopulations exhibit phenotypic changes which favor carriage or invasive disease. In particular, the spnIIIB allele has been associated with increased nasopharyngeal carriage and the downregulation of the luxS gene. The LuxS/AI-2 QS system represent a universal language for bacteria and has been linked to virulence and biofilm formation in S. pneumoniae. In this work, we have explored the link between spnIII alleles, the luxS gene and virulence in two clinical pneumococcal isolates from the blood and cerebrospinal fluid (CSF) of one pediatric meningitis patient. The blood and CSF strains showed different virulence profiles in mice. Analysis of the spnIII system of these strains recovered from the murine nasopharynx showed that the system switched to different alleles commensurate with the initial source of the isolate. Of note, the blood strain showed high expression of spnIIIB allele, previously linked with less LuxS protein production. Importantly, strains with deleted luxS displayed different phenotypic profiles compared to the wildtype, but similar to the strains recovered from the nasopharynx of infected mice. This study used clinically relevant S. pneumoniae strains to demonstrate that the regulatory network between luxS and the type 1 restriction-modification system play a key role in infections and may support different adaptation to specific host niches.